Peranan Jaksa Penuntut Umum dalam Pengembalian Barang Bukti Kepada Pihak Korban Tindak Pidana di Wilayah Hukum Kejaksaan Negeri Tanjung Jabung Timur - Nuraini, Nuraini; Kartika, Olivia Nindy (Wajah Hukum, 2024)
The criminal act committed is very closely related to the evidence or goods, while the evidence will be used to prove the criminal act committed before the court by the prosecutor. An item of evidence will be presented at the evidentiary hearing at trial. Regarding evidence, if the trial verdict states that the evidence will be returned to the party who has the rights, then this action is carried out by the prosecutor in accordance with his authority in implementing the judge's verdict which already has permanent legal force and the basis for this implementation is guided by the quote from the judge's decision. This research aims to study the legal regulations on the implementation of the judge's decision regarding the return of evidence and examine the obstacles to returning evidence to its owner by prosecutors. This type of research is empirical juridical research that uses primary data through interviews with the East Tanjung Jabung state prosecutor's office, as well as secondary data obtained through analysis of secondary, primary and tertiary legal materials. From the results of the research, it was concluded that the legal regulations regarding the process of returning evidence for criminal acts in the jurisdiction of the East Tanjung Jabung district court have gone through a process that involves determining the legal force of the decision and making a letter extracting the judge's decision. Generally, an extract of the decision is issued within approximately one week after the inkracht decision. The prosecutor will receive an excerpt from the decision to prepare a BAP for the judge's decision and prepare a BA for the return of evidence. Then the evidence will be handed over to the individual whose name is listed in the text of the decision made by the judge. There are no time provisions governing the collection of evidence by the owner whose name has been mentioned in the contents of the verdict, so the prosecutor must immediately return the evidence, this is due to concerns that the evidence could pile up at the Prosecutor's Office.